Gastrodin blocks neural stem cell differentiation into glial cells mediated by kainic acid - Sun, Guifang; Yuan, Zhihao; Zhang, Boai; Jia, Yanjie; Ji, Yangfei; Ma, Xingrong; Liu, Yu; Liu, Yanru; Wen, Quanqing; Zhao, Yanling (Neural regeneration research, 2012)
Kainic acid can simulate excitatory amino acids in vitro. Neural stem cells, isolated from newborn Wistar rats, were cultured in vitro and exposed to 100 4 000 #M kainic acid for 7 days to induce neuronal cell differentiation, causing the number of astrocytes to be significantly increased. Treatment with a combination of 0.5 mg/L gastrodin and kainic acid also caused the number of differentiated neurons to be significantly increased compared with treatment with kainic acid alone Experimental findings suggest that gastrodin reduces the excitability of kainic acid and induces neural stem cell differentiation into neurons.